The suppression of periodic vortex shedding from a rotating circular cylinder - Dol, Sharul sham; Kopp, G.; Martinuzzi, R. (Elsevier, 2008)
An experimental study of the turbulent near wake of a rotating circular cylinder was made at a Reynolds number of 9000 for velocity ratios, ?=OD/(2U8), between 0 and 2.7. Analysis of hot-wire anemometry data from the near wake indicates that the periodic vortex shedding is suppressed for ?=~2.0. It was also observed that the Strouhal number and convection speed of the vortices increases with the velocity ratio up to suppression of the vortex street. The spacing ratio of the vortices remains constant while there is a vortex street. After suppression of the street, it is observed that the convection speeds of the two rows of vortices differ while the spacing ratio diminishes. These results are consistent with an earlier stability analysis taking into account the inequality of the two shear layers. In addition, increased inequality of the two separated shear layers leads to weaker vortices in the near wake region. © 2007 Elsevier Ltd. All rights reserved.